2018
DOI: 10.1186/s12879-018-3486-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of infectious spondylitis after vertebroplasty, and comparisons between pyogenic and tuberculosis

Abstract: BackgroundInfection after vertebroplasty (VP) is a rare but serious complication. Previous literatures showed most pathogens for infection after VP were bacteria; tuberculosis (TB) induced infection after VP was extremely rare. We reported our treatment experiences of cases with infectious spondylitis after VP, and compared the differences between developed pyogenic and TB spondylitis.MethodsFrom January 2001 to December 2015, 5749 patients had undergone VP at our department were reviewed retrospectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
0
24
2
Order By: Relevance
“…It requires major salvage surgery and may lead to residual disability and even death in several cases. In addition to standard skin preparation and the administration of prophylactic antibiotics, surgeons should preoperatively consider immune status, urinary tract infection or other infection source within 6 months, and history of pulmonary tuberculosis to prevent infection post vertebroplasty [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It requires major salvage surgery and may lead to residual disability and even death in several cases. In addition to standard skin preparation and the administration of prophylactic antibiotics, surgeons should preoperatively consider immune status, urinary tract infection or other infection source within 6 months, and history of pulmonary tuberculosis to prevent infection post vertebroplasty [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize procedure-related infection while still providing an appropriate clinical benefit, it was safer to proceed with a lumbar TFESI, a quicker, lower-risk intervention with minimal needle manipulation and less equipment-patient interaction compared to a VA, which is a longer, higher-risk, more elaborate procedure with multiple device exchanges involving needle entry from the skin into the pedicle and vertebral body, which potentially increases the risk of infection complications. Infection rates vary in the literature, but the VA has been found to have more than twice the relative risk compared to ESIs [ 31 , 32 , 33 ]. Particularly in a relatively immunocompromised patient, it is prudent to minimize risk of potentially life-threatening infection.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Infection after vertebroplasty rarely occurs. Liao et al [10] reported the incidence of infection after vertebral augmentation is between 0% and 1%. Infection was ruled out in the present case by laboratory and pathological examination.…”
Section: Discussionmentioning
confidence: 99%